Korelasi Alih Fungsi Lahan DAS Padolo Terhadap Frekuensi dan Dampak Kerugian Bencana Banjir di Kota Bima (Periode 2017–2024) - Sulaiman Sulaiman (Pelantar Press, 2026)
The Padolo Watershed (DAS), which spans Bima Regency and Bima City, is the main focus of hydrological disaster issues in West Nusa Tenggara (Nusa Tenggara Barat). This study aims to analyze the correlation between land cover change within the Padolo Watershed and the increase in the frequency and damage caused by flood disasters in Bima City during the 2017–2024 period. The methodology employed is a mixed-method analysis, involving qualitative literature review and quantitative time-series data analysis from BMKG (Agency for Meteorology, Climatology, and Geophysics) and BPBD (Regional Disaster Management Agency) data, coupled with a spatial analysis approach using land cover data from Esri | Sentinel-2 Land Cover Explorer. The results indicate significant land cover changes from 2017 until 2024, characterized by an increase in Built Area from 2,195 Ha to 2,904 Ha and a corresponding loss of natural forest land (Trees) from 8,283 Ha to 6,245 Ha. These alterations correlate with a high frequency and impact of disasters, which peaked in 2021 with 12 flood incidents and 3,427 submerged houses (Indonesian Disaster Data Geoportal). Bima City's naturally concave topography (often described as a 'water bowl') is further exacerbated by the degradation of critical land in the upstream area, resulting in persistent flood disasters even during years with relatively lower rainfall intensity. This analysis underscores the necessity of restoring the Padolo Watershed's carrying capacity through integrated, policy-supported management